Growth and productivity of direct-seeded basmati rice (Oryza sativa L.) as influenced by sowing dates and irrigation schedules in north-western India - Diljeet Kaur; Angrej Singh; Vinay Kumar Sindhu (Agricultural Water Management, 2024)
Due to water shortage and rising irrigation costs in rice cultivation regions, the adoption of water-saving technologies, such as direct-seeded rice, has become imperative for ensuring sustainable rice production. Thus, the present study was conducted to investigate the influence of sowing dates and irrigation schedules on the growth and productivity of direct-seeded basmati rice (DSBR). The experiment was laid out in split plot design keeping combinations of two sowing dates (June 10 and June 20) and time of first irrigation (7, 14 and 21 days after sowing, DAS) in main plots and subsequent irrigation schedules at 1.25, 1.50 and 1.75 IW/ETc, irrigation water to crop evapotranspiration ratio in sub-plots. The results revealed that delay in sowing of DSBR from June 10 to June 20 did not significantly reduce the yield attributes and grain yield. However, DSBR sown on June 20 required less irrigation (1280 mm) compared to June 10 (1326 mm) while the apparent crop water productivity (ACWP) remained statistically similar. Delaying the first flood irrigation from 7 to 21 DAS did not significantly impact DSBR yield or its attributes but reduced cultivation costs (CC) by US$ 24–31. This delay saved approximately 17.1 % of irrigation water, enhanced ACWP and reduced deep drainage losses by 220–279 mm without affecting actual crop evapotranspiration. Subsequent irrigation schedules significantly influenced DSBR yield and attributes, with an IW/ETc of 1.50 and 1.75 performing better than an IW/ETc of 1.25 in terms of panicle count, grains per panicle, grain yield and ACWP. However, increasing irrigation frequency from IW/ETc of 1.50–1.75 did not enhance yield parameters or grain yield but increased CC by US$ 23–24 and significantly reduced ACWP. IW/ETc of 1.50 saved 11.7 % (175 mm) of irrigation water compared to IW/ETc of 1.75. In conclusion, delaying the direct sowing of basmati rice to June 20, postponing the first irrigation until 21 DAS, and scheduling subsequent irrigations at 1.50 IW/ETc are effective strategies. Crucially, these interventions do not significantly reduce grain yield but instead contribute to water savings, reduced cultivation costs, and lower water footprints.